Microfinance providers and rural lending in the province of Carniola before 1914 - Hönig, Nataša (Prispevki za novejšo zgodovino, 2024)
The study provides new insights and compares two different types of microfinance intermediaries and their role and impact on the economic and financial situation of the rural population before the beginning of World War I. The abolition of serfdom in the Habsburg monarchy in 1848 had a significant impact on traditional life in the second half of the 19th century. Peasants became landowners, and their participation in the market and monetary economy became crucial. The development of microfinance intermediaries, such as savings banks and credit cooperatives, was essential for the financial inclusion of the rural population. The article shows the development of credit operations in a rural environment using the example of the District Credit Cooperative Litija.
Keywords: 18. st.; 19. st.; credit cooperatives; District Credit Cooperative Litija; history; hranilnice; kreditiranje podeželja; kreditne zadruge; microfinance; mikrofinance; Okrajna posojilnica Litija; savings banks; zgodovina